Improving Student Learning Outcomes Using the Flipped Classroom Learning Model - Khairani, Nova; Tanjung, Indayana Febriani; Rohani (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2022)
This study aims to determine the effect of the Flipped Classroom learning model on student learning outcomes on Environmental Pollution material in Al-Hijrah Integrated Islamic Junior High School Medan. This research is a quantitative research (quasi-experimental). The population in this study were all class VII IT Al-Hijrah Junior High School Medan, totaling 94 students. The sample taken in this study was random sampling consisting of two classes, namely class VII-AB Ikhwan as an experimental class and class VII-B Ikhwan as a control class with 16 students in each class. Based on the results of data analysis, the average pretest value of the experimental class was 40.42 including the low category, the posttest average value of 81.0 including the high category. While the average pretest for the control class is 40.00, including the low category and the average score for the posttest for the control class is 61.67, including the low category. The results of hypothesis testing tarithmetic = 5.35 > ttable = 2.04 with probability = 0.05 and dk = 30. With the conclusion that the hypothesis H0 rejected and the hypothesis Ha is accepted, because tcount > ttable = 5.35 > 2.04. This shows that there is an effect of using the flipped classroom learning model on student learning outcomes.